Decoupled Single Farm Payments of the CAP and Land Rental Prices - Paul Feichtinger; Klaus Salhofer (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2016)
This paper contributes to the discussion on the extent of the capitalization of decoupled direct payments into land rental prices. Based on a dynamic panel model and an extensive dataset for Bavaria for 2005 to 2011, we show that a significant number of Single Farm Payments (SFPs) of the European Union (EU) Common Agricultural Policy (CAP) are captured by landowners rather than by active farmers. However, the degree of capitalization varies considerably among regions, from almost 0 to 56 cents per each additional Euro paid.
Keywords: H22; Q15; Q18; 330; capitalization; decoupled subsidies; Common Agricultural Policy; land rental prices